Two Different Extranodal Lymphomas in an HIV+ Patient: A Case Report and Review of the Literature - Clara Bertuzzi; Elena Sabattini; Francesco Bacci; Claudio Agostinelli; Gian Gaetano Ferri (Case Reports in Hematology)
Human immune deficiency virus- (HIV-) infected individuals present a higher risk of developing malignancies. Herein, we are presenting an unusual case of an untreated HIV+ patient, who developed two distinct lymphoproliferative disorders in a period of 4 years: a primary cutaneous T-cell lymphoma (PCTCL) and a diffuse large B-cell lymphoma (DLBCL) not otherwise specified (NOS), the latter developed while commencing combined antiretroviral therapy (cART). The two lymphomas also showed peculiar features: PCTCL are rarely described in HIV+ setting and particularly at such a low clinical stage, and the DLBCL showed uncommon cytology, non-GCB phenotype, EBER negativity, and absence of c-MYC translocation, all atypical features in this clinical context. This report not only confirms the increased risk of lymphoma for HIV+ patients and HIV infection being one of the major risk factors for lymphoid disorders but draws the attention on the possible occurrence of unusual features, suggesting that HIV serology should always be investigated in the clinical suspicion of lymphoma.